Facial Bone Contouring Surgery A Practical Guide (Springer Singapore, 2018)
This book is a practical and detailed guide on how to perform a range of surgical techniques for facial bone contouring. Based on the clinical experiences gained by the authors while carrying out more than 10,000 facial bone surgeries at their clinical institute in Seoul, Korea, each procedure is meticulously described and illustrated, step by step. Importantly, careful attention is paid to the impact of ethnic differences on surgical technique and goals, drawing on lessons learned during the treatment of patients from approximately 30 countries. Readers will also find instructive accompanying case studies and copious guidance on preoperative patient assessment, potential complications, and complication management. Facial bone contouring surgery has been gaining popularity not only in many Asian countries but also in Western countries, especially those in which there are sizable Asian populations. In enabling readers to learn and master the various techniques of facial bone surgery, and to achieve optimal outcomes in clinical practice, the book will be of immense value to plastic surgeons in both Asia and the West.